2016
DOI: 10.1080/00102202.2016.1193499
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Detonation Control Using a Pulse Hot Jet in Supersonic Combustible Mixture

Abstract: Abstract:To investigate the mechanism of detonation control using a pulse hot jet in the supersonic hydrogen-oxygen mixture, high-resolution simulations with a detailed reaction model were conducted using an adaptive mesh refinement method. After the successful detonation initiation, a contractive passway was generated between the hot jet and the main flow field behind the detonation front. Due to the contractive passway, the expansion of detonation products was prevented, hence resulting in overdriven detonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…As a result, as shown in Fig. 2c, detonation attenuation results in a reduction of numbers of both transverse waves and triple points [43]. Compared with that in Fig.…”
Section: A Detonation Attenuation and Interaction With The Cavitymentioning
confidence: 70%
See 4 more Smart Citations
“…As a result, as shown in Fig. 2c, detonation attenuation results in a reduction of numbers of both transverse waves and triple points [43]. Compared with that in Fig.…”
Section: A Detonation Attenuation and Interaction With The Cavitymentioning
confidence: 70%
“…It should be noted that if no cavity is embedded in the channel, the attenuated detonation will finally fail and disappear in the channel [43]. Based on this comparison, it is suggested that the cavity-based setup plays an important role in the relatively dynamical sustainment propagation of detonation in supersonic combustible mixtures.…”
Section: Periodical Propagationmentioning
confidence: 99%
See 3 more Smart Citations